O5. Monte Carlo study on megavolt X-ray therapy dosimetry for nanoparticle dose enhancement. (September 2016) - Mutsakanyi, S.; du Plessis, F.
Abstract : Introduction: Nanoparticles (NPs) are emerging as promising agents for cancer therapy to enable dose enhancement during X-ray photon therapy. This study employs Monte Carlo (MC) as the most suitable tool to simulate dose distribution in water and patient CT phantom using DOSXYZnrc an EGSnrc based MC code. Materials and Methods: DOSXYZnrc was used to characterize BEAMnrc modelled x-ray photon beams obtained from full simulation of a 6MV Elekta Precise treatment head. It modelled a 40 × 40 × 40 cm 3 cubic water phantom with a source-to-surface distance of 100 cm. It was divided into 200 dose scoring voxels set at 0.2 cm size each in all three x, y and z directions respectively. Depth dose distributions were calculated for a range of field sizes and depths. Once the beams were characterized, the DOSXYZnrc code was used to calculate the dose scored in a realistic patient CT phantom. This phantom contained the prostate as the delineated PTV that contained gold NPs for dose enhancement. In some cases these NPs where removed from the PTV to study the dose impact. Simulations were run using 3DCRT with necessary histories ensuring uncertainty is below 1%. Results: DOSXYZnrc successfully modelled a mathematical cubic water phantom and allowed extraction of PDDs and planar dose files for modelled photon beams. A patient CT phantom was successfully modelled. Significant dose enhancement of 9% was obtained. MCSHOW program enable the displays and calculation of dose profiles in CT phantom. Conclusion: We can conclude that MC simulation of radiation transport is one of the most accurate methods of radiation therapy dose calculation in both homogeneous and inhomogeneous medium. The results uncertainty can be easily managed since it is statistically based.